Factors Associated With Reproductive Health Knowledge Among Vocational School Students In Padang - Yuliza, Wilda Tri; Yanti, Meyi; Alkafi, Alkafi; Rahma, Gusni (Preventia : The Indonesian Journal of Public Health, 2023)
The Ministry of Health of the Republic of Indonesia in 2022 reported that 35.3 persen of women and 31.2 persen of men aged 15-19 have limited or no awareness of reproductive health. The rise of vocational students who are often caught in raids with several cases including sexual deviations is a fatal impact of the lack of reproductive health knowledge on adolescence. The purpose of this study is to find out the factors associated with reproductive health knowledge among vocational students in Padang City. A cross-sectional quantitative research was conducted in July-September 2023 among 538 students at SMK in Padang, with a sample of 85 people selected using stratified random sampling technique. Data was collected through a questionnaire with an interview method, and univariate and bivariate analysis was performed using the chi-square test. The study found a significant relationship between parental role (p equal to 0.037), peer influence (p equal to 0.018), and media influence (p equal to 0.018) with reproductive health knowledge in vocational students. It is recommended that students seek information from trusted sources related to reproductive health, to ensure accurate and useful understanding.